Design and simulation of filter banks by using signal flow graphs - Zhang, Xinhang (2019)
Multi-rate filter banks play an important role in the field of signal processing. Many filter bank designs have been proposed. However, these design methods of filter banks are often derived based on mathematical derivations and in general, a design method of a filter bank tends to be for one specific application. This makes the design approach difficult to be extended for a more general filter bank structure. In addition, complex mathematical derivations make users without enough related background difficult to understand.